Clinical evaluation of reasons for replacement of amalgam vs composite posterior restorations - Ayah A Al-Asmar; Alaa HA Sabrah; Islam M Abd-Raheam; Noor H Ismail; Yara G Oweis (Saudi Dental Journal)
Background: The aim of the present study is to evaluate the most common reasons for replacing posterior amalgam and resin composite restorations in patients attending the university dental restorative clinics. Methods: A total of 318 restorations which needed to be replaced were clinically and radiographically evaluated in a period of nine months. The frequencies of reasons for replacing posterior amalgam and resin composite restorations were calculated; secondary caries, restoration/tooth fracture, marginal discoloration/ditching, proximal overhang/open margin, loss of anatomy, pain/sensitivity, and esthetics. Results: The sample population comprised of 191 females and 106 males. The majority of the sample population fell in the age group of 40–50 years (n = 110). 318 restorations (n = 318) were examined in this study. 82% of examined teeth were restored with amalgam (n = 261), while posterior composite restorations comprised 18% of the examined teeth (n = 57). Among all restorations demanded to be replaced by the patients (n = 318), aesthetic need was the most common reason (n = 98), followed by Ditching or discoloration (n = 64), secondary caries (n = 57), and fracture (n = 44). Loss of anatomy was the least common cause to replace both amalgam and resin composite restorations (n = 5). The different reasons of failure were all significant between amalgam and resin composite restorations as shown in (Fig. 1) (p < 0.005). The most common reason for amalgam replacement was aesthetic. The most common reason for composite replacement was secondary caries and marginal ditching. Conclusion: Both amalgam and composite had different reasons for replacement. Amalgam had lesser risk of developing secondary caries and higher longevity than composite.